Replenishment of Hepatitis B Virus cccDNA Pool Is Restricted by Baseline Expression of Host Restriction Factors In Vitro - Brezgin, Sergey (Microorganisms, 2019)
Background: Covalently closed circular DNA (cccDNA) of hepatitis B virus (HBV) is the major cause of viral persistence in patients with chronic HBV infection. Understanding the mechanisms underlying stability and persistence of HBV cccDNA in hepatocytes is critical for developing novel therapeutics and managing chronic hepatitis B. In this study, we observed an unexpected increase in HBV cccDNA levels upon suppression of transcription by de novo DNA methyltransferase DNMT3A and uncovered additional mechanisms potentially involved in HBV cccDNA maintenance. Methods: HBV-expressing cell lines were transfected with a DNMT3A-expressing plasmid. Real-time PCR and HBsAg assays were used to assess the HBV replication rate. Cell cycling was analyzed by fluorescent cell sorting. CRISPR/Cas9 was utilized to abrogate expression of APOBEC3A and APOBEC3B. Alterations in the expression of target genes were measured by real-time PCR. Results: Similar to previous studies, HBV replication induced DNMT3A expression, which in turn, led to reduced HBV transcription but elevated HBV cccDNA levels (4- to 6-fold increase). Increased levels of HBV cccDNA were not related to cell cycling, as DNMT3A accelerated proliferation of infected cells and could not contribute to HBV cccDNA expansion by arresting cells in a quiescent state. At the same time, DNMT3A suppressed transcription of innate immunity factors including cytidine deaminases APOBEC3A and APOBEC3B. CRISPR/Cas9-mediated silencing of APOBEC3A and APOBEC3B transcription had minor effects on HBV transcription, but significantly increased HBV cccDNA levels, similar to DNMT3A. In an attempt to further analyze the detrimental effects of HBV and DNMT3A on infected cells, we visualized γ-H2AX foci and demonstrated that HBV inflicts and DNMT3A aggravates DNA damage, possibly by downregulating DNA damage response factors. Additionally, suppression of HBV replication by DNMT3A may be related to reduced ATM/ATR expression. Conclusion: Formation and maintenance of HBV cccDNA pools may be partially suppressed by the baseline expression of host inhibitory factors including APOBEC3A and APOBEC3B. HBV inflicts DNA damage both directly and by inducing DNMT3A expression.